Buprenorphine/naloxone treatment practices in Malaysia: Results of national surveys of physicians and patients. (1st July 2015) - Vicknasingam, B.; Dazali, M.N.M.; Singh, D.; Schottenfeld, R.S.; Chawarski, M.C.
Highlights: General practitioners in Malaysia have limited training in addiction and Buprenorphine/naloxone. (Bup/Nx) treatment. Bup/Nx dosages are low, not optimal, provided without monitoring or drug counseling. Bup/Nx patients continue heroin use and injection drug use during treatment. Abstract: Objective: Medication assisted treatment with buprenorphine/naloxone (Bup/Nx), including prescribing and dispensing practices of general practitioners (GPs) in Malaysia and their patients' experiences with this treatment have not been systematically examined. The current study surveyed GPs providing Bup/Nx treatment and patients receiving office-based Bup/Nx treatment in Malaysia. Methods: Two cross-sectional surveys of GPs ( N  = 115) providing outpatient Bup/Nx maintenance treatment and of patients ( N  = 253) currently receiving Bup/Nx treatment throughout peninsular Malaysia. Results: Physicians prescribed Bup/Nx dosages in the range of 2–4 mg daily for 70% of patients and conducted urine testing in the past month on approximately 16% of their patients. In the patient survey, 79% reported taking daily Bup/Nx doses of 2 mg or less; 82% reported that no urine toxicology testing had been conducted on them in the past month, 36% had an opiate positive urine test at the time of the survey, 43% reported illicit opiate use, 15% reported injection of heroin and 22% reported injection of Bup/Nx in the past month. Conclusion: Low daily Bup/Nx doses, lack of behavioral monitoring or counseling, and high rates of continued drug use, including injection of drugs and medications during Bup/Nx treatment in Malaysia, indicate continuing problems with implementation and less than optimal treatment effectiveness. High cost of Bup/Nx in Malaysia may deter patients from seeking treatment and contribute to taking low Bup/Nx dosages. Improved training of physicians and establishing standards for Bup/Nx dosing, routine toxicology testing, and counseling may be needed to improve care and treatment response.